A common variant of CDKN2A (p16) predisposes to breast cancer. Issue 10 (6th May 2005) - Dębniak, T; Górski, B; Huzarski, T; Byrski, T; Cybulski, C; Mackiewicz, A; Gozdecka-Grodecka, S; Gronwald, J; Kowalska, E; Haus, O; Grzybowska, E; Stawicka, M; et al.
Abstract : Background: A common missense variant of the CDKN2A gene (A148T) predisposes to malignant melanoma in Poland. An association between malignant melanoma and breast cancer has been reported in several families with CDKN2A mutations, Objective: To determine whether this variant also predisposes to breast cancer. Methods: Genotyping was undertaken in 4209 cases of breast cancer, unselected for family history, from 18 hospitals throughout Poland and in 3000 controls. Results: The odds ratio (OR) associated with the CDKN2A allele for women diagnosed with breast cancer before the age of 50 was 1.5 (p = 0.002) and after age 50 it was 1.3 (p = 0.2). The effect was particularly strong for patients diagnosed at or before the age of 30 (OR = 3.8; p = 0.0002). Conclusions: CDKN2A appears to be a low penetrance breast cancer susceptibility gene in Poland. The association should be confirmed in other populations.